Analysis of Work Measurement Using the Stopwatch Time Study Method at PTEA - masniar masniar; Umar Rusli Marasabessy; Engelberto Astrides; Asih Ahistasari; Mohammad Arief Nur Wahyudien; Mirga Maulana Rachmadhani (Journal of Industrial System Engineering and Management, 2023)
In the era of globalization or the world of free trade, competition in the industrial world is increasing rapidly, this causes business competition to increase. Seeing the importance of measuring every activity carried out by the company, an accurate measurement method is needed to be able to provide accurate information on the time needed and the efficiency of each product activity in meeting production targets to achieve profits. The Stopwatch Time Study method is a work measurement technique using a stopwatch as a means of measuring the time shown in the completion of an observed activity. From the measurement results, a standard time will be obtained to complete a work cycle, where this time will be used as a standard for completing work for all workers who will carry out the same work as that. To determine the standard time, first calculate the cycle time and the time normal considering the degree of adjustment and allowance. Based on the results of data processing and discussion, it can be concluded that the lowest normal time is for employee 2 with a time of 39.05 seconds. Employee adjustment factor 2 with a total adjustment of +0.12 and employee allowance factor 2 with a total allowance of 22.